The Effect of Composition Variation of Pineapple, Squeezed Orange (Citrus sinensis), and Tomato on The Electrical Properties of Voltaic Cells as an Electrolyte Solution - Trianadewi, Dina; Abadi, Hilda Yanuar; Ainisyifa, Zia Nazaliah; Siswanto, Adam; Anggraeni, Sri; Nandiyanto, Asep Bayu Dani (ASEAN Journal of Science and Engineering, 2023)
This study aims to demonstrate the electrolyte solution from the fruits to be used as electrical source energy. We combined and varied the composition of the pineapple, squeezed orange, and tomato. The novelties of this research are (1) investigation of the composition of three electrolyte solutions, such as pineapple, squeezed orange, and tomato; (2) the use of these electrolytes. Experiments were done by designing the experimental apparatus and mixing fruits with different compositions. The fruits were mashed using a saw-milling apparatus. We made a series of electrical circuits to test the electrolyte solution. Data were collected every hour for 5 h. We tested the voltage, current strength, and pH. In the circuit, we used a small LED light (2 volts) for ensuring the electrical ability. The results of this study showed the presence of a voltage and current generated, turning on the LED. The more volume of the squeezed orange increased the citric acid, resulting the electrolyte solution to be more acidic (less pH). The utilization of fruits such as pineapple, squeezed orange, and tomato is effective as an electrolyte solution.